EXAMINING JOB DEMANDS AS A MEDIATOR: UNRAVELING THE INFLUENCE OF ENTREPRENEURIAL ACTIVITIES ON JOB BURNOUT - Hardaningtyas , Ratna; Amin, Sirojuddin (Jurnal Riset Bisnis dan Manajemen, 2024)
Given that burnout can have detrimental effects on both entrepreneurs and their businesses, it is crucial to comprehend how job demands affect burnout among entrepreneurs. Understanding the causes of burnout can help entrepreneurs manage their workload and resources more skillfully, which can improve both their personal and professional success. According to data from the Office of Cooperatives and Micro Businesses of Malang City, Indonesia, 126 respondents who were registered as "entrepreneurs" in this study employed structural equation modeling (SEM). The main finding of this study is that job demands play an important role in influencing the level of job burnout among entrepreneurs. The study also found that solo entrepreneurs can experience motivation and stress in running their business, and they can create their own resources over time, reflecting their efforts in managing their business.